New strategies for optimized structural monitoring of wind farms: experimental campaign - J. Pacheco; S. Guimarães; C. Moutinho; M. Marques; J. C. Matos; F. Magalhães (Wind Energy Science, 2020)
The main goal of the recently started WindFarmSHM research project is the development, validation and optimization of monitoring strategies to be applied at the level of the wind farm. These strategies should be able to evaluate the structural condition of a set of wind turbines and their consumed fatigue life using the response to operation loads. In this context, a quite extensive experimental campaign is being performed at the Tocha wind farm, an onshore wind farm located in Portugal, which includes the simultaneous instrumentation of several wind turbines, adopting strain gauges, clinometers and accelerometers distributed in the tower and blades. This paper introduces the Tocha wind farm, presents the different layouts adopted in the instrumentation of the wind turbines and shows some initial results from the already fully instrumented wind turbine. At this preliminary stage, the capabilities of the very extensive monitoring layout are demonstrated. The results presented in this paper demonstrate the ability of the different monitoring components to track the modal parameters of the system composed of a tower and rotor and to characterize the internal loads at the tower base and blade roots.